2017
DOI: 10.1101/216242
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The microbiome and resistome of hospital sewage during passage through the community sewer system

Abstract: 2 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
(66 reference statements)
0
1
0
Order By: Relevance
“…Antibiotic residues in hospital wastewaters may reach levels that potentially could be selective for resistant strains [25][26][27]. Several studies have accordingly shown that hospital effluents can provide a rich variety of known ARGs and resistant enteric pathogens [28][29][30][31][32]. It is therefore plausible that a more explorative analysis could lead to the discovery of novel ARGs, either easily accessible to pathogens or already circulating among pathogens undetected.…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic residues in hospital wastewaters may reach levels that potentially could be selective for resistant strains [25][26][27]. Several studies have accordingly shown that hospital effluents can provide a rich variety of known ARGs and resistant enteric pathogens [28][29][30][31][32]. It is therefore plausible that a more explorative analysis could lead to the discovery of novel ARGs, either easily accessible to pathogens or already circulating among pathogens undetected.…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater is any water from different processing and manufacturing operations such as pharmaceuticals, agriculture, domestic sources, and healthcare centres, whose quality have been tainted by a high level of anthropogenic influence [7]. The hospital wastewater is however quite different from wastewater from other sources because it contains a vast number of micro-and macro-pollutants, which have been discharged from the different departments of hospitals including laboratories, theaters, laundries, research units and other notable sections [8].…”
Section: Wastewater From Healthcare Systems (Composition and Microbio...mentioning
confidence: 99%
“…In some instances, some pharmaceuticals present in hospital wastewater have been implicated in causing the disruption of the endocrine system, impairment of the reproductive system and sex reversal in some aquatic species [10]. The discharge of this wastewater has led to the build-up of nutrients in the receiving aquatic ecosystem, leading to eutrophication [7].…”
Section: Wastewater From Healthcare Systems (Composition and Microbio...mentioning
confidence: 99%